Genetic and phenotypic characterization of the novel mouse substrain C57BL/6N Korl with increased body weight. Issue 1 (December 2017) - Choi, Kyung-Min; Jung, Jaehoon; Cho, Young; Kim, Kwondo; Kim, Mi-Gyeong; Kim, Jinho; Kim, Huibae; Shin, Hee; Kim, Hae; Chung, Seung-Tae; Cho, Seoae; Chung, Myeon-Woo
Abstract In inbred mouse lines, there is generally little genetic difference between individuals. This small genetic variability facilitates carrying out research on minute changes of various traits and the gene pool. Also, characterizing the diversity and detecting selective genetic and phenotypic signatures are crucial to understanding the genomic basis of a population and to identify specific patterns of evolutionary change. In this study, we investigated the underlying genetic profiles of a newly developed mouse strain, C57BL/6NKorl (Korl), established through sibling mating over 30 generations. To analyse the distinctive genomic features of Korl mice, we used whole-genome sequencing from six samples, which were compared to those of other C57BL/6N-based mouse strains. Korl strain-specific polymorphisms were identified and signatures of a selective sweep were detected. In particular, the candidate genes related to the increased body weight of the Korl strain were identified. Establishment of the genetic profile of Korl mice can provide insight into the inbreeding-induced changes to the gene pool, and help to establish this strain as a useful model for practical and targeted research purposes.